2018
DOI: 10.1111/jphp.13047
|View full text |Cite
|
Sign up to set email alerts
|

Study of nuclear factor-2 erythroid related factor-2 activator, berberine, in paclitaxel induced peripheral neuropathy pain model in rats

Abstract: Objectives The role of nuclear factor‐2 erythroid related factor‐2 (Nrf2) activator, berberine (BBR), has been established in rat model of streptozotocin induced diabetic neuropathy. Around 30–40% of cancer patients, on paclitaxel (PTX) chemotherapy develop peripheral neuropathy. The present study was contemplated with the aim of establishing the neuropathy preventive role of BBR, in paclitaxel induced peripheral neuropathy model in rats. Methods A total of 30 Wistar rats were divided into five groups as follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 37 publications
(95 reference statements)
2
22
0
Order By: Relevance
“…PT enhances neuronal free radical production. Abundant accumulation of cytosolic free radicals is known to activate lipid peroxidation of the neuronal membrane [33]. In the present study, lipid peroxidation products (TBARS) levels were estimated by a spectrophotometric method [47].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PT enhances neuronal free radical production. Abundant accumulation of cytosolic free radicals is known to activate lipid peroxidation of the neuronal membrane [33]. In the present study, lipid peroxidation products (TBARS) levels were estimated by a spectrophotometric method [47].…”
Section: Discussionmentioning
confidence: 99%
“…Ayurvedic herbs have large quantities of GA [26,30,31]. Experimentally, GA has been documented to produce anti-hyperlipidemic, cardioprotective, anti-diabetic activity [32,33]. Furthermore, GA has potential neuroprotective action due to mono and poly-targeted actions [34,35].…”
Section: Introductionmentioning
confidence: 99%
“…2) [78]. Singh et al [87] found that berberine was effective in ameliorating the heat hyperalgesia and cold allodynia. Morphometric analysis of sciatic nerves revealed that berberine treatment significantly increased axon diameter and myelin thickness, but the axon number did not be increased compared with the paclitaxel group.…”
Section: Regulation Of Alkaloids On Oxidative Stress In Cipn Rodentsmentioning
confidence: 99%
“…In oxidative stress, genes encoding antioxidant defending enzymes are activated, especially the nuclear erythroid 2-related factor 2 (Nrf2) gene, which increases the expression of SOD, glutathione peroxidase (GSH-Px), and catalase genes [ 88 ]. Berberine exerted analgesic and neuroprotective effects via upregulating Nrf2 mRNA and further enhancing antioxidant capacity in the sciatic nerve [ 87 ].
Fig.
…”
Section: Effects Of Alkaloids Chemotherapy-induced Peripheral Neuropamentioning
confidence: 99%
“…48,50,66 Brb has great efficacy in the treatment of neurological disorders. Sing et al 55 evaluated the protective effects of Brb in paclitaxel (PTX)-induced peripheral neuropathy pain model in rats. They exhibited that Brb administration is associated with an increase in the tail-flick, tail cold allodynia latencies as well as a reduction in histopathological score.…”
Section: Neuroprotective Effect Of Berberine Mediated By Nrf2 Signamentioning
confidence: 99%